2020
DOI: 10.1002/lt.25869
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Computed Tomography Angiography Demonstrates a High Burden of Coronary Artery Disease Despite Low‐Risk Nuclear Studies in Pre–Liver Transplant Evaluation

Abstract: We investigated the presence and severity of coronary artery disease (CAD) in orthotopic liver transplantation (OLT) candidates using coronary artery calcium score (CACS) and coronary computed tomography angiography (CCTA) as compared with the prevalence of normal and abnormal single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI). A total of 140 prospective OLT candidates without known CAD underwent coronary artery calcium (CAC) scans with (n = 77) or without CCTA and coronary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Several studies have suggested the potential role of coronary artery calcium (CAC) to estimate the cardiovascular risk of patients undergoing LT [4][5][6][7]. Other investigations have compared CAC evaluation to non-invasive stress tests (such as exercise testing or nuclear studies) demonstrating its higher correlation with the burden of coronary artery disease [8,9]. Quantification of CAC usually requires dedicated chest computed tomography (CT) scans that are thin-layer (usually slices of 3 mm) and electrocardiography (ECG) gated, in order to minimize motion artifacts from beating heart and to provide better quality images.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested the potential role of coronary artery calcium (CAC) to estimate the cardiovascular risk of patients undergoing LT [4][5][6][7]. Other investigations have compared CAC evaluation to non-invasive stress tests (such as exercise testing or nuclear studies) demonstrating its higher correlation with the burden of coronary artery disease [8,9]. Quantification of CAC usually requires dedicated chest computed tomography (CT) scans that are thin-layer (usually slices of 3 mm) and electrocardiography (ECG) gated, in order to minimize motion artifacts from beating heart and to provide better quality images.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in a recent study, when CCTA findings were correlated with SPECT MPI, nearly all ESLD patients were found having a normal SPECT MPI result. This finding indicates that CCTA may serve as a more effective gatekeeper to improve efficiency of referral to CA [57]. The authors also reported high eligibility for FFR-CT analysis due to acceptable CT image quality in these patients with impaired hemodynamic profiles, while this issue is also being addressed by the ongoing CRASCH-Liver trial (www.clinicaltrials.gov Identifier: NCT04089969).…”
Section: Cctamentioning
confidence: 95%
“…Invasive coronary angiography is the gold-standard test to identify significant CHD in the general population, but currently, in LT candidates, studies are inconclusive and not able to predict the impact of asymptomatic pre-LT CV abnormalities on long-term outcomes [ 39 , 40 ]. Coronary computed tomography angiography (CCTA) is a non-invasive test valid for assessing the risk of CHD in LT candidates, although no studies are comparing it with invasive coronary angiography (ICA) in this population [ 41 ]. CCTA alone does not provide a functional assessment of coronary stenosis, which can be obtained by integrating this examination with fractional flow reserve obtained from computed tomography in this population [ 42 ].…”
Section: Pre-transplant Evaluationmentioning
confidence: 99%